2018
DOI: 10.3897/mycokeys.44.30295
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of soil-inhabiting Trichoderma from southwest China

Abstract: Fungi in the genus Trichoderma are widely distributed in China, including in Yunnan province. In this study, we report three new soil-inhabiting species in Trichoderma, named as T.kunmingense, T.speciosum and T.zeloharzianum. Their colony and mycelial morphology, including features of asexual states, were described. For each species, their DNA sequences were obtained from three loci, the internal transcribed spacer (ITS) regions of the ribosomal DNA, the translation elongation factor 1-α encoding gene (tef1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 45 publications
1
34
0
1
Order By: Relevance
“…The genus Trichoderma Pers., introduced by Persoon (1794), is cosmopolitan, including saprotrophs and mycoparasites in a diversity of ecosystems, such as agricultural fields, prairies, forests, salt marshes, and fungal fruiting body ( Gazis and Chaverri 2010 ; Chaverri et al 2015 ; Qiao et al 2018 ). Species of this genus have been widely used in the biocontrol of plant pathogens ( Chaverri et al 2015 ; Degenkolb et al 2015 ; Bunbury-Blanchette and Walke 2019) and production of enzymes and bioactive compounds ( Sun et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The genus Trichoderma Pers., introduced by Persoon (1794), is cosmopolitan, including saprotrophs and mycoparasites in a diversity of ecosystems, such as agricultural fields, prairies, forests, salt marshes, and fungal fruiting body ( Gazis and Chaverri 2010 ; Chaverri et al 2015 ; Qiao et al 2018 ). Species of this genus have been widely used in the biocontrol of plant pathogens ( Chaverri et al 2015 ; Degenkolb et al 2015 ; Bunbury-Blanchette and Walke 2019) and production of enzymes and bioactive compounds ( Sun et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some of them are associated with green mold diseases in the commercial production of mushrooms ( Innocenti et al 2019 ; Sun et al 2019a ) . Morphologically, the asexual-morphs are similar in producing branched tree-like conidiophores with cylindrical to nearly subglobose phialides and ellipsoidal to globose conidia, but their variation is insufficient to differentiate the Trichoderma species ( Chaverri et al 2015 ; Qin and Zhuang 2017 ; Qiao et al 2018 ). Multilocus molecular phylogeny, based on combined sequence data of the internal transcribed spacer ( ITS ) regions, RNA polymerase II subunit ( RPB2 ), and the translation elongation factor 1-α gene ( TEF1-α ), enables rapid and accurate identification of the Trichoderma species ( Druzhinina et al 2005 ; Atanasova et al 2013 ; Chaverri et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new genus and species, Blastosporium persicolor Z.F. Yu & H. Zheng has been described and illustrated from leaves of mildewed tobacco [20]. Memnoniella sinensis Hua Zheng et al was identified in a deserted rocky area in Yunnan [21].…”
Section: Introductionmentioning
confidence: 99%